THE EFFECT OF BRAND AMBASSADOR AND SALES PROMOTION ON REPURCHASE INTENTION OF TOKOPEDIA CUSTOMERS IN BANDUNG, INDONESIA - Mohammad, Anriera Raihan; Wikarto, Fitri Melliana; Assyraq, Olga; Meuraxa, Tiffani; Sari, Rania Ratna; Nilasari, Irma (CENTRAL ASIA AND THE CAUCASUS, 2022)
Marketplace competition in Indonesia is very tight, some of the top marketplaces in Indonesia: Shopee, Tokopedia, Lazada, Bukalapak and Blibli. This study focuses on Tokopedia which is ranked second in the Top Brand Award (2021). This study aims to examine the repurchase intention of Tokopedia customers based on two independent research variables: brand ambassador and sales promotion. 138 valid respondents were involved in data processing. Hypothesis testing found that brand ambassadors and sales promotions have a positive effect on repurchase intention.